A voyage with Hitchcock - Pomerance, Murray, 1946- (SUNY Press, 2021)
"Extensive meditations on the theme of the voyage in six Hitchcock films: Psycho, The 39 Steps, The Birds, Dial M for Murder, Rich and Strange, and Suspicion"--